Comparison of Effectiveness between Dexamethasone and Clonidine as an Adjuvant to Bupivacaine for Ultrasound-Guided Supraclavicular Brachial Plexus Block in Patients undergoing Upper Limb Surgery (Journal of Enam Medical College, 2026)
Background: The supraclavicular brachial plexus (SBPB) block is widely used for upper limb surgeries. Adding adjuvants such as dexamethasone and clonidine to bupivacaine may enhance its efficacy. This study evaluates and compares these adjuvants in terms of improved peripheral nerve blocks by reducing the onset time, improving the efficacy of the block during surgery and extending postoperative analgesia block, postoperative analgesia. Objective: This study was designed for the evaluation of the effectiveness of dexamethasone versus clonidine as an adjuvant to bupivacaine for ultrasound-guided supraclavicular brachial plexus block in patients undergoing upper limb surgery. Materials and Methods: This randomized controlled trial was conducted on 75 adult patients undergoing upper limb surgeries at Dhaka Medical College Hospital. Patients were divided into three groups: Group A (bupivacaine + normal saline), Group B (bupivacaine + dexamethasone), and Group C (bupivacaine + clonidine). Outcomes assessed included onset and duration of sensory and motor block, time for first demand of analgesia and total consumptions of analgesics within 24 hours, haemodynamic parameters, adverse effects were observed among three groups. Data were analyzed using ANOVA and t-tests, with statistical significance set at p0.05).The time for complete sensory block was 23.6±3.1, 18.9±3.2 and 14.7±3.0 minutes and time for the onset of maximum motor level was 29.5±3.9, 23.5±3.1 and 20.8±2.4 minutes in Group A, B and C respectively. These are significantly less in clonidine (group C) group compared to normal saline (group A) and dexamethasone (group B) group (p